2019
DOI: 10.1101/671222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entorhinal velocity signals reflect environmental geometry

Abstract: The entorhinal cortex contains neural signals for representing self-location, including grid cells that fire in periodic locations and velocity signals that encode an animal's speed and head direction. Recent work revealed that the size and shape of the environment influences grid patterns. Whether entorhinal velocity signals are equally influenced or provide a universal metric for self-motion across environments remains unknown. Here, we report that changes to the size and shape of the environment result in r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Two candidates for such a speed signal terminating in the MEC have been proposed: a speed signal by firing rate, most clearly present in a subpopulation of "speed cells" showing positive and linear speed tuning curves (Kropff et al, 2015); and an oscillatory speed signal by changes in LFP theta frequency or by changes in the theta rhythmic firing frequency of individual MEC neurons (Burgess, 2008;Hinman et al, 2016). Both speed signals can change in response to changes of the size and shape of the environment (Munn et al, 2020), as do grid cells (C. Barry et al, 2007;Krupic et al, 2015). In this study, we examined how changes in spatial stability of grid cells relate to Notably, the observed saturating exponential component in changes of grid cell spatially periodic firing supports an earlier report by Pérez-Escobar et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Two candidates for such a speed signal terminating in the MEC have been proposed: a speed signal by firing rate, most clearly present in a subpopulation of "speed cells" showing positive and linear speed tuning curves (Kropff et al, 2015); and an oscillatory speed signal by changes in LFP theta frequency or by changes in the theta rhythmic firing frequency of individual MEC neurons (Burgess, 2008;Hinman et al, 2016). Both speed signals can change in response to changes of the size and shape of the environment (Munn et al, 2020), as do grid cells (C. Barry et al, 2007;Krupic et al, 2015). In this study, we examined how changes in spatial stability of grid cells relate to Notably, the observed saturating exponential component in changes of grid cell spatially periodic firing supports an earlier report by Pérez-Escobar et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Grid cells are thought to provide a universal, that is, environment-invariant, metric for spatial navigation based on the use of idiothetic cues (McNaughton et al, 2006). It has since been shown that the grid map is not as environmentindependent as previously assumed (Barry et al, 2007(Barry et al, , 2012Boccara et al, 2019;Derdikman et al, 2009;Jacob et al, 2019;Krupic et al, 2015;Munn et al, 2020). Yet, the MEC-grid cellspath integration hypothesis remains predominant despite the fact that only a few studies have shown a link between grid cell activity and path integration (Allen et al, 2014;Gil et al, 2018;Jacob et al, 2019) and between the MEC and path integration (Jacob et al, 2017;Van Cauter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our framework also provides algorithmic-and implementation-level explanations for observed features of grid cell firing in response to manipulations 7,9,[21][22][23][24] or inhomogeneity [25][26][27][28][29] of environmental sensory input. Overall, these phenomena can be understood in a probabilistic framework, where minimization of prediction errors between the transition and observation models are traded against prior model beliefs.…”
Section: Introductionmentioning
confidence: 99%